Evaluation of antenatal simulation-based learning on satisfaction and self-confidence levels among Thai undergraduate nursing students during the COVID-19 pandemic: a mixed-method study - Kornkanok Kuesakul; Sasitara Nuampa; Rudee Pungbangkadee; Lucie Ramjan; Ameporn Ratinthorn (BMC, 2024)
Abstract Background During the COVID-19 pandemic, simulation-based learning (SBL) serves as an alternative teaching strategy for nursing students facing restricted access to antenatal clinical practicum. However, the factors predicting nursing students' satisfaction, self-confidence, and their learning experiences remain unclear. Objective To identify factors predict satisfaction and self-confidence and explore the learning experiences of antenatal SBL. Methods A Mixed methods research of the cross-sectional study design and descriptive qualitative research was conducted. A total of 100 third year nursing students who finished the Maternity-Newborn Nursing and Midwifery Practice course using antenatal simulation-based learning were invited to complete the online questionnaires. A total of seven questionnaires were administered, including a demographic questionnaire, the Attitude Scale toward Simulation-Based Education (SBE), the Professional Identity Scale for Nursing Students, the Perceived Stress Scale, the Evaluation of Teaching Competencies Scale, the Simulation Design Scale: Student Version, and the Student Satisfaction and Self-Confidence in Learning. The 20 nursing students who completed survey were asked to participate a qualitative focus group discussion. Multiple regression analysis was performed to investigate predictors, while qualitative data were analyzed using content analysis. Results The quantitative results showed high levels of satisfaction (mean = 20.55, SD = 3.17) and self-confidence (mean = 32.44, SD = 4.76) after completing the antenatal SBL. In regression analysis, attitude toward SBE (Beta = 0.473, t = 5.376, p < 0.001) and attitude toward antenatal care simulation design (Beta = 0.338, t = 2.611, p < 0.011) were significantly associated with a high level of satisfaction with antenatal SBL, which accounted for 44.0% of the variance explained in satisfaction. Only attitude toward SBE was significantly associated with a high level of self-confidence in antenatal SBL (Beta = 0.331, t = 3.773, p < 0.001), which accounted for 45.0% of the variance explained in self-confidence. The qualitative results generated four themes: (1) positive attitude toward antenatal simulation; (2) turning reassurance into confidence; (3) I am really happy to learn; and (4) being a good nurse motivates and stresses me. Conclusions Antenatal SBL is an effective teaching strategy that can support nursing students to build clinical confidence. Creating a positive learning environment allows students to have a positive attitude and experience with simulations.